Rotary Shaft Seals: Correlation of Wear Formation at the Sealing Edge and Shaft under Various Operating Conditions. Issue 5 (25th August 2022) - Merkle, Lukas; Baumann, Matthias; Bauer, Frank
Abstract: Elastomeric rotary shaft seals are a common seal type for various industrial applications. They are comparably cheap and easy to use and offer an overall good performance. But the wear behavior of these sealing systems is not fully understood and not predictable so far. If a lip seal fails, it causes high maintenance costs and environmental damage. In this article, various tribological conditions are considered. For this purpose, the sealing systems are tested with multiple operating conditions relevant to practice. Three test series are conducted with rotary shaft seals BAUM5X7 75FKM585 on plunge ground shafts. The tests are carried out with two different circumferential velocities of the shaft (4.2 and 10 m/s), three different oil sump temperatures (40, 80, and 120 °C), two different lubricant types (FVA 3 and PG 3), and five different test durations (between 100 and 625 h). For a complete acquisition of the system condition, all shaft surfaces are measured in 2D and 3D before and after the test runs and the wear of the sealing edges is evaluated with a recently developed laser line triangulation method on the complete circumference of the sealing rings. Results show large amounts of wear, depending significantly on the operating conditions. A strong correlation of the wear effects in the tribocontact area of the sealing system becomes evident. This article helps to understand and avoid critical operating conditions concerning abrasive wear.